PENGARUH KONSENTRASI ETANOL SEBAGAI PELARUT PENGEKSTRAKSI TERHADAP KADAR NAFTOKINON DALAM EKSTRAK DAUN PACAR KUKU (Lawsonia inermis L.) - Zainab, Zainab (Universitas Ahmad Dahlan, 2013)
The extract quality can be affected by the components and concentration of chemical compounds containedin the extract.Type and quantities of chemical compounds that are dissolved in the extraction process is stronglyinfluenced by the solvent extraction. The aim of this study is to determine the effect of concentration of ethanol assolvent extraction on naphthoquinone content in Henna leaves extract. The extraction method was done bymaceration for one hours with water, ethanol 50% , 70% , 90% and 95% v/v solvens of the dried Henna leavespowder. Each macerate was made 5 % w/v concentration and than was spotted 5 ÂµL on plate of silica gel F 254 andeluted with mixture of chloroform - methanol (17:3 v/v) as mobile phase. The spots on chromathogram werescanning and measured the area under curve with TLC densitometer at maximum wave lenght. The results showedthat spot at Rf 0.31 had similar spectra with naphthoquinone standard and same maximum wavelength at 279 nm.The result of solvent optimization indicated that the best solvent extraction for Henna leaves was ethanol 50% v/vwith the highest naphthoquinone contentat 1.43 Â± 0.1942% w/v.